Investigating the development of number sense in a 6th grade class in Taiwan - Reys, Robert E.; Yang, Der-Ching (NOMAD Nordic Studies in Mathematics Education, 2005)
This research study reports snapshots of a 6th grade Taiwanese class depicting how a teacher investigated and promoted his students’ development of number sense. It illustrates students’ tendency to rely on written algorithms and reveals some misconceptions that may exist among students that are generally proficient in written computation. It demonstrates an effort to integrate number sense activities into the mathematics class in ways that encourage exploration, discussion, thinking, and reasoning.